Comparación de la retención de selladores de fosas y fisuras a base de ionómero de vidrio y resinas. revisión de la literatura - Araujo Tapia, María Fernanda (2025)
Introduction: Fissure and cavities sealants are essential for preventing caries on posterior dental surfaces. This systematic review compares the retention of glass ionomer and resin-based sealants, two common materials in clinical practice. Objective: To compare the retention of resin-based and glass ionomer pit and fissure sealants through a literature review. Methodology: Studies published between 2018 and 2023 in databases such as PubMed y Scielo were reviewed. Articles comparing both types of sealants were included and evaluated following PRISMA criteria. Methodological quality and retention results were analyzed. Results: Resin-based sealants showed greater retention compared to glass ionomer sealants. At 6 months, the retention of resin-based sealants was between 90%, while glass ionomer sealants had a retention rate of 85%. At 12 months, resin-based sealants maintained a retention rate of 80% whereas glass ionomer sealants ranged from 75%. Conclusion: Resin-based sealants offer better long-term retention compared to glass ionomer sealants. The choice of material should consider not only retention but also other clinical factors such as fluoride release and application techniques.